Mitochondrial changes caused by LDL in hippocampal neurons. (31st December 2021) - Farias, Hemelin Resende; Martins, Leo; Beber, Lílian Corrêa Costa; Rodrigues, Matheus Scarpatto; Guma, Fátima; de Oliveira, Jade
Abstract: Background: Familial hypercholesterolemia (FH) is characterized by high plasma accumulation of low‐density lipoproteins (LDL) due to mutations in the LDL receptor gene (Hobbs et al., Hum. Mutat., 1: 445‐466, 1992). Furthermore, FH patients present a high incidence of cognitive impairments (Zambón et al., Am J ed, 123:267‐274, 2010; Ariza et al., Eur J Intern Med., 34:e29‐e31, 2016). Experimental studies also demonstrated that FH leads to an increase in blood‐brain‐barrier permeability (De Oliveira et al., J Alzheimers Dis, 78:97‐115, 2020), which could allow the LDL to pass from the peripheral system to the central nervous system. Importantly, the cellular mechanisms responsible for neurotoxicity induced by LDL are unclear. Herein, we aimed to investigate whether LDL causes mitochondrial alterations in neurons. Method: We exposed HT‐22 cells (Mouse Hippocampal Neuronal Cell) to human isolated LDL (50 and 300 ug/mL) for 24 hours. Furthermore, mass and potential mitochondrial were evaluated by Mitotracker green (MTG) and red (MTR), respectively, and the reactive species generation was evaluated by DCF. Result: Notably, when HT‐22 cells were incubated with LDL (50 ug/mL), MTR fluorescence was decreased compared with control cells. The ratio between MTG and MTR fluorescence showed increased mitochondria mass compared to their activity, suggesting an increase of swollen and non‐functional mitochondria. We observed in HT‐22 cells exposed to LDL (300 ug/mL) that both MTG, MTR, and ratio MTR/MTG were decreased, suggesting mitochondrial dysfunction. It is known that mitochondrial dysfunction leads to the excessive production of reactive species, and this may cause damage to essential cell components. In this regard, next, we evaluated the reactive species formation using DCF. The reactive species formation was significantly increased in cells exposed to both concentrations of LDL (50 and 300 ug/mL) in two times of exposure (1 and 24 hours) compared with the control cells. Conclusion: These findings indicate that LDL causes mitochondrial dysfunction, which appears to be a relevant event in hypercholesterolemia‐induced cerebral dysfunction.